Patients' Satisfaction After Surgical Facial Reconstruction or After Rehabilitation With Maxillofacial Prosthesis - Goiato, Marcelo Coelho [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; de Faria Almeida, Daniel Augusto [UNESP]; Inatomi Kavano Sanchez, Daniela Mayumi [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Lippincott Williams & Wilkins, 2011)
The matching of the aesthetic, functional, and psychosocial results of a facial deformity may produce devastating effects in its carriers, especially if the lesion is extensive or the treatment is aggressive. Because of this, the objective of the present article was to evaluate patient's satisfaction rating after surgical facial reconstruction or rehabilitation with oral and maxillofacial prosthesis, by means of reviewing the literature.
Keywords: Maxillofacial prosthesis; patient satisfaction; surgical facial reconstruction